Modified carbon nanotube forest, carbon nanotube continuum, conductive member and interlayer heat conductive material

JP2024052746A5Active Publication Date: 2025-01-31株式会社シーディアイ
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024014780
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-22
Filing Date
2024-02-02
Publication Date
2025-01-31
Estimated Expiration
2041-11-24

AI Technical Summary

Technical Problem

Existing methods for producing carbon nanotube forests and continuums face challenges in achieving spinnability and uniform modification with fine particles, leading to difficulties in creating conductive and thermally conductive materials with optimal properties.

Method used

A modified carbon nanotube forest is produced by supporting fine particles on oriented carbon nanotubes with a specific ratio of adjacent gap to particle diameter, allowing for spinning and subsequent plating to enhance conductivity and thermal conductivity, resulting in a conductive member and interlayer thermal conductive material.

Benefits of technology

The modified carbon nanotube forest and continuum exhibit enhanced spinnability, conductivity, and thermal conductivity, making them suitable for applications such as catalyst electrodes in fuel cells and interlayer thermal conductive materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a modified carbon nanotube forest having a structure in which a carbon nanotube forest supports fine particles.SOLUTION: A modified carbon nanotube forest 40 comprises carbon nanotubes 50 oriented in a predetermined direction and fine particles 70 supported on the carbon nanotubes 50 and is spinnable, and preferably has a ratio R of 3 or more, the ratio defined by formula (1) using an adjacent gap D1 of the carbon nanotubes 50 and an average particle size D2 of the fine particles 70. The fine particles 70 are preferably electrically conductive. R=D1 / D2 (1). The adjacent gap D1 is represented by the following formula (2) using a number density A (unit: book / m2) of the modified carbon nanotube forest 40 and an average diameter D3 of the carbon nanotubes 50. D1=A-1 / 2-D3 (2).SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a modified carbon nanotube forest (modified CNT forest), a carbon nanotube continuous body (CNT continuous body) comprising a spun body of the modified CNT forest, a gas-permeable sheet comprising the CNT continuous body, a catalyst electrode of a fuel cell comprising the gas-permeable sheet, a conductive member and a filamentary conductive member comprising the above-mentioned modified CNT forest or CNT continuous body, an interlayer thermal conductive material comprising the above-mentioned conductive member, and a method for producing the above-mentioned modified CNT forest. [Background technology]

[0002] In this specification, "CNT forest" refers to a type of synthetic structure of multiple carbon nanotubes (CNTs) (hereinafter, the individual shape of the CNTs that gives such a synthetic structure is referred to as the "primary structure", and the above synthetic structure is also referred to as the "secondary structure"), and refers to an aggregate of CNTs that are grown so that multiple CNTs are oriented in a certain direction (a specific example is a direction approximately parallel to a normal line of one of the surfaces of the substrate) for at least a part of the longitudinal direction. Patent Document 1 and Non-Patent Document 1 disclose a method for producing a CNT forest using iron chloride (gas-phase catalytic method). Non-Patent Document 2 discloses a method for obtaining a CNT forest by providing catalyst fine particles on a substrate and growing CNTs from the catalyst fine particles (solid-phase catalytic method).

[0003] In addition, in this specification, a structure in which multiple CNTs are connected to each other along the spinning direction, formed by continuously drawing out multiple CNTs from the CNT forest by pinching some CNTs in the CNT forest and pulling the CNTs away from the CNT forest (in this specification, this operation is also called "spinning" following the operation of producing yarn from fibers in the prior art), is called a "CNT continuum". Patent Document 2 discloses a secondary structure in which multiple CNTs are connected to each other along the spinning direction, and have a thread-like overall shape (in this specification, this CNT continuum is called a "CNT yarn"). The CNTs that make up the CNT yarn are oriented along the extension direction of the CNT yarn (corresponding to the spinning direction). Patent Document 2 also discloses a secondary structure in which multiple CNTs are connected to each other along the overall web-like shape (in this specification, this CNT continuum is called a "CNT web"). The CNTs that make up the CNT web are oriented along one of the in-plane directions of the CNT web (corresponding to the spinning direction). FIG. 29 shows a CNT web being spun from a CNT forest produced by a gas-phase catalytic method.

[0004] Patent Document 3 discloses a carbon nanotube electrode comprising: a plurality of carbon fibers extending along an extension direction, each of the carbon fibers containing a carbon nanotube; and a plurality of metal particles supported on the plurality of carbon fibers, the plurality of metal particles being dispersed throughout the carbon fibers in the extension direction and electrically connecting each carbon fiber to other carbon fibers.

[0005] Patent Document 4 discloses a metal composite carbon nanotube twisted yarn in which metal-coated nanotube fibers in which the surfaces of carbon nanotube fibers in which the ends of multiple carbon nanotubes are joined together are twisted together, and the contact portions of the metal coated on the carbon nanotube fibers are fused together. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2009-196873 A [Patent Document 2] Patent No. 5664832 [Patent Document 3] JP 2020-102352 A [Patent Document 4] JP 2018-53408 A [Non-patent literature]

[0007] [Non-Patent Document 1] Adrian Ghemes, Yoshitaka Minami, Junichi Muramatsu, Morihiro Okada, Hidenori Mimura, Yoku Inoue. Fabrication and mechanical properties of carbon nanotube yarns spun from ultra-long multi-walled carbon nanotube arrays. Carbon 2012;50:4579-4587. [Non-Patent Document 2] Toshiya Kinoshita, Motoyuki Karita, Takayuki Nakano, Yoku Inoue. Two step floating catalyst chemical vapor deposition including in situ fabrication of catalyst nanoparticles and carbon nanotube forest growth with low impurity level. Carbon 2019;144:152-160. Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention aims to provide a modified CNT forest in which a CNT forest is modified with other substances, a CNT continuous body comprising a spun body of the modified CNT forest, a gas-permeable sheet comprising the CNT continuous body, a catalyst electrode of a fuel cell comprising the gas-permeable sheet, a conductive member and a filamentary conductive member comprising the above-mentioned modified CNT forest or CNT continuous body, an interlayer thermal conductive material comprising the conductive member, and a method for producing the above-mentioned modified CNT forest. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention includes the following aspects. [1] A modified carbon nanotube forest, comprising carbon nanotubes oriented in a predetermined direction and microparticles supported on the carbon nanotubes, and characterized in that it is spinnable.

[0010] [2] The modified carbon nanotube forest described in [1] above, wherein the ratio R defined by the following formula (1) using the adjacent gap D1 of the carbon nanotubes and the average particle size D2 of the microparticles is 3 or more. R=D1 / D2 (1) Here, the adjacent gap D1 is the number density A (unit: tubes / m 2 ) and the average diameter D3 of the carbon nanotubes, and are expressed by the following formula (2), where the average particle size D2 and the average diameter D3 are the arithmetic mean of the diameters of the microparticles at 10 or more locations and the arithmetic mean of the diameters of the carbon nanotubes at 10 or more locations, respectively, measured by observing the modified carbon nanotube forest using an electron microscope. D1=A -1 / 2 -D3 (2)

[0011] [3] The modified carbon nanotube forest described in [1] or [2] above, wherein the microparticles are conductive.

[0012] [4] A modified carbon nanotube forest described in any one of [1] to [3] above, wherein the microparticles include an oxide.

[0013] [5] A carbon nanotube continuous body comprising a spun body of a modified carbon nanotube forest described in any one of [1] to [4] above.

[0014] [6] The continuous carbon nanotube body according to [5] above, wherein the continuous carbon nanotube body has a web shape.

[0015] [7] The carbon nanotube continuum according to [5] above, wherein the carbon nanotube continuum has a thread-like shape.

[0016] [8] The carbon nanotube continuum according to [7] above, which is twisted.

[0017] [9] A carbon nanotube continuous body having a web shape as described in [6] above, wherein at least a part of the carbon nanotubes constituting the carbon nanotube continuous body are adjacent to each other with gaps in a direction intersecting the orientation direction of the carbon nanotubes. A gas permeable sheet characterized by:

[0018]

[10] The gas permeable sheet according to the above [9], wherein the carbon nanotubes support fine particles containing one or more elements selected from the group consisting of Pt and Co.

[0019]

[11] A catalyst electrode for a fuel cell comprising the gas permeable sheet according to [9] or

[10] above.

[0020]

[12] A conductive member comprising a modified carbon nanotube forest described in any one of [1] to [3] above, and a plating-based substance deposited on carbon nanotubes located inside the modified carbon nanotube forest.

[0021]

[13] An interlayer thermally conductive material comprising the conductive member described in

[12] above.

[0022]

[14] A conductive member comprising a carbon nanotube continuous body as described in any one of [5] to [8] above, and a plating substance deposited on the carbon nanotubes located inside the carbon nanotube continuous body.

[0023]

[15] The conductive member according to the above

[14] , wherein the carbon nanotubes of the carbon nanotube continuum support conductive particles.

[0024]

[16] A method for producing a modified carbon nanotube forest according to any one of [1] to [4] above, comprising: supplying a metal element-containing substance in a gaseous state to a carbon nanotube forest; decomposing the metal element-containing substance to produce a metal-based substance; and supporting the microparticles formed from the metal-based substance on the carbon nanotube forest.

[0025]

[17] A filamentary conductive member comprising a continuous carbon nanotube body having a thread shape as described in [6] or [7] above, and a plating-based substance deposited on at least a portion of the carbon nanotubes constituting the continuous carbon nanotube body.

[0026]

[18] Current capacity is 10 5 A / cm 2 The above is the filamentous conductive member according to

[17] above.

[0027]

[19] When measuring the longitudinal conductivity, the temperature coefficient of resistance was found to be 1.8×10 in the range from 300K to 450K. -3 K -1 The filamentous conductive member according to

[17] or

[18] above, which is:

[0028]

[20] A filamentary conductive member according to any one of

[17] to

[19] above, having a specific conductivity calculated based on the conductivity measured in the longitudinal direction that is higher than the specific conductivity of a copper wire at 400 K or higher.

[0029]

[21] A filamentary conductive member described in any one of

[17] to

[20] above, having a tensile strength of 1.0 times or more and a Young's modulus of 1.5 times or more based on a blank carbon nanotube continuous body corresponding to the material excluding the plating-based substance from the filamentary conductive member. Effect of the Invention

[0030] The present invention provides a modified CNT forest, a CNT continuous body comprising a spun body of the modified CNT forest, a gas-permeable sheet comprising the CNT continuous body, a catalyst electrode of a fuel cell comprising the gas-permeable sheet, a conductive member and a filamentary conductive member comprising the above-mentioned modified CNT forest or CNT continuous body, an interlayer thermal conductive material comprising the above-mentioned conductive member, and a method for producing the above-mentioned modified CNT forest. [Brief description of the drawings]

[0031] [Figure 1] FIG. 1 is a conceptual diagram showing an example of a manufacturing apparatus for obtaining a modified CNT forest from a CNT forest. [Diagram 2] This figure shows the results of observing a portion of the side of a CNT forest. [Diagram 3] FIG. 1 shows the results of observing a portion of the side of a modified CNT forest. [Figure 4] FIG. 4 is a partially enlarged view of FIG. [Diagram 5] FIG. 5 is a diagram showing a result of observing the side surface shown in FIG. 4 by a backscattered electron image. [Figure 6] FIG. 1 shows the results of observing a portion of a cross section obtained by removing a portion of the CNT forest. [Figure 7] FIG. 7 is a diagram showing the result of observing the side surface shown in FIG. 6 by a backscattered electron image. [Figure 8]FIG. 1 is a conceptual diagram showing how a modified CNT forest is spun. [Figure 9] (a) A diagram showing the process of twisting the CNT yarn obtained by spinning the modified CNT forest to produce a CNT twisted yarn, and (b) a conceptual diagram showing the configuration of the device for spinning the modified CNT forest. [Figure 10] FIG. 1 shows the observation results of CNT twisted yarn. [Figure 11] FIG. 11 is a partially enlarged view of FIG. [Figure 12] (a) Observation image of the cross section of a CNT twisted yarn, (b) A partially enlarged image of the central part of the cross section of Figure 12(a) observed using backscattered electrons. [Figure 13] FIG. 1 is a schematic diagram showing the configuration of an apparatus for plating a CNT twisted yarn by electroplating in a copper sulfate bath. [Figure 14] FIG. 1 shows the observation results of a modified CNT forest. [Figure 15] FIG. 1 shows the observation results of a modified CNT forest. [Figure 16] FIG. 1 shows the observation results of a modified CNT forest. [Figure 17] FIG. 1 shows the observation results of a modified CNT forest. [Figure 18] 1 is a histogram showing the measurement results of particle diameters of fine particles. [Figure 19] FIG. 2 is an observation view of the appearance of a conductive member. [Figure 20] FIG. 20 is an enlarged view of the conductive member of FIG. 19. [Figure 21] FIG. 2 is an observational view of a cross section of a conductive member produced by plating at a current density of 5 mA / cm2. [Figure 22] FIG. 2 is an observation view showing a cross section of a comparative conductive member produced without modification with copper fine particles. [Figure 23] 23(a) is an observational view showing a cross section of a conductive member produced by plating at a current density of 4 mA / cm2, and (b) is a partially enlarged observation of the central portion of the cross section of FIG. 23(a). [Figure 24]FIG. 2 is an observational view showing a cross section of a comparative conductive member without modification with copper fine particles. [Diagram 25] 1 is a graph showing the measurement results of the electrical conductivity (unit: S / cm) of a conductive member. [Figure 26] 1 is a graph showing the measurement results of the specific conductivity (unit: S·m2·kg-1) of a conductive member. [Figure 27] 1 is a graph showing the measurement results of the current capacity (unit: A / cm2) of a conductive member. [Figure 28] 1 is a graph showing the measurement results of the specific current capacity (unit: A·cm·kg-1) of a conductive member. [Figure 29] This shows the state in which a CNT web is spun from a CNT forest produced by a gas-phase catalytic method. [Figure 30(A)] This is a secondary electron image of a CNT forest carrying copper nanoparticles, produced using 10 mg of Cu(acac)2. [Figure 30(B)] FIG. 1 shows a secondary electron image of a CNT forest carrying copper nanoparticles, produced using 30 mg of Cu(acac)2. [Figure 30(C)] This is a secondary electron image of a CNT forest carrying copper nanoparticles, produced using 100 mg of Cu(acac)2. [Figure 31(A)] FIG. 13 is a cross-sectional secondary electron image of a composite yarn in which copper is precipitated on a CNT twisted yarn carrying Cu-NPs. [Figure 31(B)] FIG. 13 is a cross-sectional secondary electron image of a composite yarn in which copper has been precipitated on a CNT twisted yarn not carrying Cu-NPs. [Figure 32(A)] FIG. 13 is a transmission electron image of an orthogonal cross section of a composite yarn in which copper has been deposited on a CNT twisted yarn carrying Cu-NPs. [Figure 32(B)] FIG. 33 is a high-magnification image of FIG. 32(A). [Figure 33(A)] FIG. 13 is a transmission electron image of a parallel cross section of a composite yarn in which copper is deposited on a twisted CNT yarn carrying Cu-NPs. [Figure 33(B)] FIG. 34 shows a high magnification image of FIG. 33(A). [Figure 34(A)] 1 is a graph showing the electrical conductivity of a composite yarn in which copper is deposited on a CNT twisted yarn carrying Cu-NPs and a composite yarn in which copper is deposited on a CNT twisted yarn not carrying Cu-NPs. [Figure 34(B)] This is a graph in which the vertical axis of FIG. 34(A) is made into a linear scale. [Diagram 35] 1 is a graph showing the temperature dependence of electrical resistivity of each sample normalized with respect to the value at 300K. [Diagram 36] 1 is a graph showing the temperature dependence of the specific conductivity of a composite yarn and a copper wire in which copper is precipitated on a CNT twisted yarn carrying Cu-NPs. [Figure 37] 1 is a graph showing the current capacity of each sample. [Figure 38] 1 is a graph showing the relationship between the specific conductivity and the specific current capacity of each sample. [Figure 39(A)] FIG. 4 is a stress-strain diagram of each sample. [Figure 39(B)] 1 is a graph showing the relationship between Young's modulus and tensile strength of various samples. [Figure 40(A)] FIG. 13 shows a secondary electron image of a tensile fracture site of a composite yarn in which copper was precipitated on a CNT twisted yarn carrying Cu-NPs. [Figure 40(B)] FIG. 13 shows a secondary electron image of a tensile fracture site of a composite yarn in which copper was precipitated on a CNT twisted yarn not carrying Cu-NPs. [Figure 41(A)] FIG. 13 is a secondary electron image of a composite yarn in which copper is precipitated on a CNT twisted yarn carrying Cu-NPs. [Figure 41(B)] FIG. 13 shows a secondary electron image of a buckling portion of a composite yarn in which copper was precipitated on a CNT twisted yarn not carrying Cu-NPs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] Hereinafter, an embodiment of the present invention will be described.

[0033] A modified CNT forest (modified carbon nanotube forest) according to one embodiment of the present invention comprises a CNT forest with CNTs oriented in a predetermined direction and fine particles supported on the CNTs, and is spinnable. The CNT forest can be produced by the production method (gas phase catalyst method) disclosed in Patent Document 1 or Non-Patent Document 1, or the production method (solid phase catalyst method) disclosed in Non-Patent Document 2. In these cases, the predetermined direction is a direction along the normal direction of the CNT forest formation surface of a substrate for forming the CNT forest.

[0034] The modified CNT forest has a ratio R of 3 or more, which is defined by the following formula (1) using the gap D1 between adjacent CNTs and the average particle size D2 of the microparticles. R=D1 / D2 (1)

[0035] Here, the adjacent gap D1 is the number density A of the modified CNT forest (unit: pieces / m 2 ) and the average diameter D3 of the CNTs, and is expressed by the following formula (2). The average particle size D2 and the average diameter D3 are the arithmetic mean of the diameters of fine particles at 10 or more locations and the arithmetic mean of the diameters of carbon nanotubes at 10 or more locations, respectively, measured by observing the modified CNT forest from the side using an electron microscope. D1=A -1 / 2 -D3 (2)

[0036] The adjacent gap D1 of the modified CNT forest can be made substantially equal to the adjacent gap D1' of the CNT forest (D1 = D1') by appropriately setting the method for supporting the fine particles. As described in Non-Patent Document 1, the adjacent gap D1' of the CNT forest produced by the gas phase catalytic method is approximately 10 13 book / m 2 Since the average diameter D3 is about 40 nm, it is about 275 nm. On the other hand, as described in Non-Patent Document 2, the adjacent gap D1' of the CNT forest produced by the solid-phase catalyst method has a number density A of 1.5 × 10 15 book / m 2The average diameter D3 is about 7 nm, so the average diameter is about 20 nm. In the solid-phase catalytic method, the number density A is 5 × 10 15 book / m 2 Since it is possible to produce a CNT forest with an average diameter D3 of about 4 nm, it is also possible to make the adjacent gap D1' about 10 nm.

[0037] It is important that the average particle diameter D2 of the fine particles is sufficiently smaller than the adjacent gap D1 from the viewpoint of ensuring stable spinnability of the modified CNT forest. Specifically, the ratio R defined by the above formula (1) is preferably 3 or more, more preferably 6 or more, even more preferably 7 or more, particularly preferably 8 or more, and extremely preferably 9 or more. If the average particle diameter D2 is large, there is a high possibility that fine particles are present between adjacent CNTs in the direction intersecting the orientation direction in the modified CNT forest so as to connect adjacent CNTs. Adjacent CNTs should be separated when spun, but when the fine particles connect adjacent CNTs as described above, it may be difficult to separate the adjacent CNTs, which may cause poor spinning.

[0038] As described above, based on Non-Patent Document 1, the adjacent gap D1' of the CNT forest produced by the gas-phase catalytic method is about 275 nm, so the ratio R is 3 or more when the average particle size D2 of the fine particles supported by the CNTs of the modified CNT forest formed from the CNT forest produced by the gas-phase catalytic method is 90 nm or less. Also, based on Non-Patent Document 2, the adjacent gap D1' of the CNT forest produced by the gas-phase catalytic method is about 20 nm, so the ratio R is 3 or more when the average particle size D2 of the fine particles supported by the CNTs of the modified CNT forest formed from the CNT forest produced by the gas-phase catalytic method is 6.7 nm or less. With the gas-phase catalytic method, it is also possible to produce a CNT forest with an adjacent gap D1' of about 10 nm, in which case the ratio R is 3 or more when the average particle size D2 of the fine particles is 3.3 nm or less.

[0039] The fine particles carried by the CNTs of the modified CNT forest may be conductive. A typical example of fine particles with conductivity is made of a metal-based material. When the fine particles are made of a metal-based material, the constituent metal elements are not particularly limited. Examples include Au, Ag, Cu, Pt, Ni, Co, Fe, Al, Ti, Zn, W, and Cr.

[0040] The fine particles supported by the CNTs in the modified CNT forest may contain oxides. Specific examples of oxides contained in the fine particles include oxides of aluminum and titanium. The fine particles may contain multiple metal elements that constitute the oxide.

[0041] The modified CNT forest according to one embodiment of the present invention may be produced by any production method as long as the CNTs of the CNT forest, which is one of the raw materials, can carry fine particles of a predetermined size and the resulting modified CNT forest has spinnability. The method described below makes it possible to efficiently produce the modified CNT forest.

[0042] A method for manufacturing a modified CNT forest according to one embodiment of the present invention comprises supplying a metal element-containing substance in a gaseous state to a CNT forest, decomposing the metal element-containing substance to produce a metal-based substance, and supporting the microparticles formed from the metal-based substance on the CNT forest.

[0043] CNT forests can be produced by known methods. Specific examples include the gas-phase catalytic method described in Patent Document 1 and Non-Patent Document 1, and the solid-phase catalytic method described in Non-Patent Document 2. CNT forests produced by these production methods can be spun.

[0044] The metal element-containing substance is a substance that can be decomposed in a gas phase and can form fine particles from the decomposition product, a metal-based substance. Examples of the metal element-containing substance include organometallic complexes such as copper(II) acetylacetonate and platinum acetylacetonate, and metal halides.

[0045] The metal element-containing substance does not need to be in a gas phase at the supply stage, and may be preferably in a solid or liquid phase from the viewpoint of improving the ease of handling. In this case, in order to put the metal element-containing substance into a gas phase state, it may be preferable to heat the metal element-containing substance or reduce the pressure in the space in which the metal element-containing substance is placed. The decomposition of the metal element-containing substance occurs by applying energy from the outside. Specifically, the metal element-containing substance may be heated, or may be irradiated with a laser or a high-energy beam such as an electron beam.

[0046] The decomposition product of the metal-containing substance, the metal-based substance, may be a metallic material including an alloy or an intermetallic compound, or may be an oxide. The generated metal-based substance aggregates or acts as an autocatalyst to form fine particles.

[0047] 1 is a conceptual diagram of an example of a manufacturing apparatus for obtaining a modified CNT forest from a CNT forest. The manufacturing apparatus 100 includes a glass tube 10, the interior of which serves as a reaction chamber RC, and a heater 20 provided to cover the side surface of the glass tube 10. A metal element-containing substance RS is placed in the reaction chamber RC, and a CNT forest 30 is placed around the metal element-containing substance RS.

[0048] The reaction chamber RC is depressurized and heated by heater 20 to put the metal element-containing material RS into a gaseous state. The metal element-containing material RS in the gaseous state diffuses and is supplied to CNT forest 30, where the metal element-containing material RS is thermally decomposed to produce a metal-based substance, and the fine particles based on the metal-based substance are supported by the CNTs of the CNT forest 30, resulting in a modified CNT forest 40.

[0049] The particle size of the microparticles can be adjusted by the amount of metal element-containing material RS placed in the reaction chamber RC, the total pressure of the reaction chamber RC, the temperature of the reaction chamber RC, etc. The specific numerical ranges of these parameters are appropriately set according to the type of metal element-containing material RS so as to realize the average particle size D2 set by the adjacent gap D1 of the modified CNT forest. It is also possible to set the loading density of the CNT microparticles by adjusting these parameters.

[0050] In the manufacturing method according to the present embodiment, the metal element-containing material, which is the raw material of the fine particles, is supplied to the carbon nanotube forest in a gaseous state, so that the modification of the CNTs by the fine particles can be generated with high uniformity for the CNTs constituting the CNT forest. That is, according to the manufacturing method according to the present embodiment, the modification of the CNTs located inside the CNT forest by the fine particles can be stably realized, and the obtained modified CNT forest can be spun. In contrast, for example, in Patent Document 2, Ag nanometal ink is dripped onto the CNT forest when manufacturing a carbon nanotube electrode. Therefore, among the CNTs constituting the CNT forest, the CNTs located on the outside are more likely to have fine particles (Ag in Patent Document 2) attached thereto, and the fine particles are less likely to attach to the CNTs located inside the CNT forest. In addition, in the method disclosed in Patent Document 2, a liquid (ink) is dripped onto the CNT forest in order to attach the fine particles to the CNTs constituting the CNT forest. At this time, the CNTs constituting the CNT forest come into contact with each other due to the cohesive force of the liquid. Since a strong interaction occurs between the CNTs in contact with each other, it is no longer possible to separate them. In other words, it is impossible for the modified CNT forest described in Patent Document 2 to be spinnable.

[0051] Figure 2 shows the results of observing part of the side of a CNT forest. In the following, unless otherwise specified, "observation" means observation with an electron microscope or optical microscope. Figure 2 is a secondary electron image. This CNT forest was produced by a gas-phase catalytic method, and its number density A is 10 13 book / m 2The average diameter D3 of the CNTs is about 35 nm. Therefore, the adjacent gap D1 of the CNT forest is about 280 nm. Figure 3 is a diagram showing the observation result of a part of the side of a modified CNT forest formed from a CNT forest produced by the same production method as the CNT forest of Figure 2. Figure 4 is a partially enlarged view of Figure 3.

[0052] As shown in FIG. 3, the CNTs in the CNT forest do not change morphologically even when they support fine particles. Therefore, the adjacent gap D1 of the modified CNT forest is substantially equal to the adjacent gap D1' of the CNT forest. The modified CNT forest shown in FIG. 3 is formed from a CNT forest produced by a gas-phase catalytic method, so the adjacent gap D1 is about 280 nm. Also, as shown in FIG. 4, the diameter of the fine particles supported on the CNTs is sufficiently smaller than 100 nm. As will be described later in the examples, the average particle size D2 of the fine particles is 29.2 nm. Therefore, in the modified CNT forest shown in FIG. 4, the ratio R is 9 or more, and it can be said that the modified CNT forest has particularly stable spinnability.

[0053] FIG. 5 is a diagram showing the results of observation of the side shown in FIG. 3 by a backscattered electron image, in which the fine particles (made of a Cu-based conductive material) attached to the CNTs are observed as bright spots. FIG. 6 is a diagram showing the results of observation of a part of a cross section (i.e., the inside of the CNT forest) obtained by removing a part of the CNT forest at a plane including the orientation direction of the CNTs. FIG. 7 is a diagram showing the results of observation of the side shown in FIG. 6 by a backscattered electron image, in which the fine particles attached to the CNTs are observed as bright spots. Comparing FIG. 5 and FIG. 7, the density of bright spots is slightly higher in FIG. 5, but a sufficient number of bright spots are also observed in FIG. 7, and it is confirmed that the modified CNT forest also supports fine particles on the CNTs located inside it.

[0054] A carbon nanotube continuous body (CNT continuous body) according to one embodiment of the present invention includes a spun body of the above-mentioned modified CNT forest. FIG. 8 is a conceptual diagram showing how a modified CNT forest is spun. CNTs 50 located on a part of the side of the modified CNT forest 40 on the substrate SB are pulled out in the direction D, so that the CNTs 50 oriented in the direction D (spinning direction) are continuously connected to form a CNT continuous body 60. As shown in FIG. 8, the fine particles 70 attached to the CNTs 50 constituting the modified CNT forest 40 maintain their state even after spinning. Therefore, the CNTs 50 constituting the CNT continuous body 60 obtained by spinning the modified CNT forest 40 are also highly uniformly modified with the fine particles 70.

[0055] The shape of the CNT continuum is determined by the spinning process, and the shape may be a web or a thread.

[0056] A web-shaped CNT continuum (CNT web) can be obtained by drawing one of the sides of the modified CNT forest so that it does not converge. The drawn CNT web can be continuously spun, for example by winding it up on a drum.

[0057] The CNTs constituting the CNT web are oriented along the spinning direction. The connection state of adjacent CNTs in the spinning direction (i.e., the orientation direction) is maintained by the van der Waals force generated between each end of the CNT and other CNTs. Therefore, the CNTs constituting the CNT web are not connected to adjacent CNTs in the direction intersecting the spinning direction (intersecting direction) at parts other than the ends, and there are gaps between adjacent CNTs in the intersecting direction. In other words, the CNTs constituting the CNT web have a mesh-like structure while being modified with fine particles. The length of this gap depends on the number density of the CNT forest and the spinning method (especially the tension when spinning), but can be set in the range of several nm to several μm, for example. Therefore, by appropriately adjusting the gaps in the CNT web, a gas-permeable sheet that allows gas to pass through but does not allow liquid to pass through can be formed.

[0058] This gas-permeable sheet is capable of generating an interaction between the gas passing through the sheet and the fine particles because the CNTs constituting the sheet are modified with fine particles. Moreover, the gas-permeable sheet is conductive in the in-plane direction. Specifically, because the CNTs are oriented in the spinning direction, the conductivity along the orientation direction is higher than the conductivity in the direction perpendicular to the orientation direction. Therefore, if an appropriate conductive catalyst material (e.g., a Pt-Co alloy containing Pt and Co) is selected as the fine particles modifying the CNTs, this gas-permeable sheet can be used as a component of the catalyst electrode of a fuel cell.

[0059] A thread-shaped CNT continuum (CNT yarn) is obtained by drawing CNTs from one side of the modified CNT forest so that a CNT web is formed, and then converging this CNT web in the spinning direction to further draw out the CNTs. The CNTs constituting the CNT yarn thus formed are oriented along the extension direction of the thread shape of the CNT yarn. For this reason, compared to a thread-shaped structure produced by, for example, ejecting a liquid containing CNTs with a short axial length from a die, the CNT yarn produced by the production method according to this embodiment has a high electrical conductivity along the extension direction of the thread shape and excellent mechanical properties.

[0060] As described above, in the modified CNT forest, the CNTs located inside are also modified with fine particles, so that even the CNTs located at the center of the CNT yarn are modified with fine particles. In contrast, in the manufacturing method disclosed in Patent Document 3, for example, a dispersion liquid containing metal particles is applied to a CNT fiber (corresponding to a CNT yarn) drawn from a CNT array (corresponding to a CNT forest), so that metal particles are attached to the CNTs. Therefore, the metal particles are more likely to attach to the CNTs located on the outer side of the CNT fiber, and metal particles are less likely to attach to the CNTs located at the center of the CNT fiber. That is, the CNT yarn manufactured by the manufacturing method according to this embodiment is more uniformly modified with fine particles than the CNT yarn manufactured by the manufacturing method disclosed in Patent Document 3.

[0061] The CNT yarn obtained by spinning may be wound on a bobbin as it is, or may be wound while being additionally processed. One of the additional processes is twisting. FIG. 9(a) is a diagram showing the state in which the CNT yarn obtained by spinning the modified CNT forest is twisted to produce a twisted yarn (CNT twisted yarn). FIG. 9(b) is a diagram conceptually showing the configuration of an apparatus for spinning the modified CNT forest. FIG. 10 is a diagram showing the observation result of the CNT twisted yarn, and FIG. 11 is a partially enlarged view of FIG. 10. FIG. 12(a) is an observation view of the cross section of the CNT twisted yarn. FIG. 12(b) is a partially enlarged view of the central part of the cross section of FIG. 12(a) observed by reflected electrons. By twisting, the mechanical strength of the CNT yarn is increased, and in some cases the electrical properties (conductivity) are improved. As shown in FIG. 11 and FIG. 12, the CNT twisted yarn is modified with fine particles even to the CNT located at the center.

[0062] A method for manufacturing a conductive member according to one embodiment of the present invention includes plating a CNT continuous body having CNTs carrying conductive microparticles as described above, and depositing a plating substance on the CNTs located inside the CNT continuous body.

[0063] The process for depositing the plating material may be electroplating or electroless plating. The plating material is appropriately set as necessary. An example of a non-limiting plating process is electroplating using a copper sulfate bath. FIG. 13 is a conceptual diagram of an apparatus for plating a CNT twisted yarn by electroplating in a copper sulfate bath. In the plating apparatus 100A shown in FIG. 13, the CNT twisted yarn 120 held by a mica sheet (mica foil) 110 is immersed in a copper sulfate bath 130, one end of the CNT twisted yarn 120 that is not immersed in the copper sulfate bath 130 is clamped by a clip 141, and the wiring 151 connected to the clip 141 is electrically connected to the cathode terminal 161 of the power source 160. An anode 170 made of a U-shaped copper foil is immersed in the copper sulfate bath 130, a part of the anode 170 that is not immersed in the copper sulfate bath 130 is clamped by a clip 142, and the wiring 152 connected to the clip 142 is electrically connected to the anode terminal 162 of the power source 160. By passing a current from a power source 160, the CNT yarn 120 is copper plated, and a conductive member 200 is obtained.

[0064] The conductive member thus obtained has sufficiently high conductivity as it is, but the conductive member can be heat-treated in a reducing atmosphere to reduce the plating material and further increase the conductivity of the conductive member. The heat treatment conditions are appropriately set, and a non-limiting example is 700°C for 1 hour under a hydrogen gas flow (100 sccm).

[0065] A conductive member according to another embodiment of the present invention includes the above-mentioned modified CNT forest and a plating substance deposited on the carbon nanotubes located inside the modified carbon nanotube forest. As described above, the CNTs constituting the modified CNT forest support fine particles generated based on the decomposition of the metal element-containing substance, so that the CNTs located inside the modified CNT forest are also modified by the fine particles. Therefore, by plating the modified CNT forest, the plating substance is deposited so as to fill the gaps in the CNT forest. If the fine particles supported by the CNTs have electrical conductivity, the deposition of the plating substance is realized more stably. If, for example, copper with high thermal conductivity is selected as the plating substance, the conductive member obtained by plating has high thermal conductivity in the extension direction of the CNTs, and can be suitably used as an interlayer thermal conductive material.

[0066] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention. EXAMPLES

[0067] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples. Example 1

[0068] A conductive member was manufactured using the manufacturing apparatus shown in FIG. 1 and the plating apparatus shown in FIG.

[0069] Using the manufacturing method disclosed in Patent Document 1 and other documents, a CNT forest with a growth height of approximately 0.8 mm was obtained on the CNT-formed surface of the substrate under the following conditions. Carbon source: Acetylene Catalyst: Solid FeCl2

[0070] The diameter of the CNTs constituting the obtained CNT forest was 30 nm to 40 nm. When the CNT-formed surface of the substrate after removing the CNT forest was observed, the number density of the CNT forest was 10 13 book / m 2 The crystallinity of the CNTs that make up the CNT forest was evaluated by Raman scattering measurement, and the ratio of the G peak intensity of the graphene in-plane vibration mode to the D peak intensity due to its disorder vibration, I G / I D was 2 to 3.

[0071] Using the manufacturing apparatus 100 shown in FIG. 1, the CNT forest 30 was modified with copper fine particles using copper (II) acetylacetonate (Cu(acac)2) as the metal element-containing substance RS to obtain a modified CNT forest. Specifically, the CNT forest 30 was placed in a sealable reaction chamber RC, and the metal element-containing substance RS, Cu(acac)2, was placed nearby. Next, the reaction chamber RC was filled with argon gas and the pressure was kept at 30 Torr. Next, the inside of the reaction chamber RC was heated at a temperature of 400°C for 15 minutes using the heater 20. The CNTs of the CNT forest 30 were modified with copper fine particles generated by the separation of Cu(acac)2 at 200°C, and the modified CNT forest 40 was obtained. The images shown in FIG. 3 to FIG. 7 are observational views of the manufactured modified CNT forest 40. The fine particles observed in these figures were made of a Cu-based conductive material.

[0072] A modified CNT forest produced by the same method was observed using a scanning transmission electron microscope to measure the diameter of the CNTs and the particle size of the microparticles. Figures 14 to 17 are figures showing the observation results of the modified CNT forest, and Figure 18 is a histogram showing the measurement results of the particle size of the microparticles. When the diameters of 13 CNTs randomly selected from the images shown in Figures 14 to 17 were measured, the average diameter (average diameter D3) was 36 nm, with a standard deviation of 8.6 nm. From the above measurement results, the number density A of the modified CNT forest was 10 13 book / m 2Therefore, the adjacent gap D1 of the modified CNT forest is 280 nm (=(10 13 m -2 ) -1 / 2 -36 nm). In addition, the particle size of 62 particles randomly selected from the images shown in Figures 14 to 17 was measured, and the average particle size (average particle size D2) was 29.2 nm, with a standard deviation of 10.7 nm. Therefore, the ratio R defined by the above formula (1) was 9.7.

[0073] The resulting modified CNT forest was spun to obtain a CNT twisted yarn as shown in Figure 9. The diameter of the resulting CNT twisted yarn was 30-35 μm.

[0074] A sample prepared by cutting a part of the obtained CNT twisted yarn was subjected to copper plating using the apparatus shown in Fig. 13. The specific conditions were as follows: Plating bath: Copper sulfate aqueous solution (Tanaka Kikinzoku Co., Ltd. "Microfab Cu300") ·Current density: 4mA / cm 2 or 5mA / cm 2 Plating time: 1 hour

[0075] The conductive member obtained by depositing copper plating on the CNT twisted yarn was heated in a hydrogen gas flow (100 sccm) at 700°C for 1 hour. Thus, the conductive member to be evaluated was obtained. Fig. 19 is an observational view of the appearance of the conductive member thus obtained, and Fig. 20 is an enlarged observational view of the conductive member's appearance.

[0076] Figure 21 shows the current density at 5mA / cm 2 FIG 22 is an observational view showing a cross section of a conductive member produced by plating a CNT forest not modified with copper fine particles with a current density of 5 mA / cm 2 FIG 23 is an observational view showing a cross section of a comparative conductive member produced by plating with a current density of 4 mA / cm 2FIG 19 is an observational view showing a cross section of a conductive member produced by plating a CNT forest not modified with copper fine particles with a current density of 4 mA / cm 2 FIG. 2 is an observational view showing a cross section of a comparative conductive member produced by plating with

[0077] As is clear from a comparison between Figures 21 and 22, and between Figures 23 and 24, by using the modified CNT forest, a conductive component was obtained in which the copper density was relatively high near the center.

[0078] By adjusting the plating conditions, we fabricated several conductive parts with different copper volume fractions (unit: vol%). The electrical conductivity (unit: S / cm) and specific conductivity (unit: S m 2 ·kg -1 ) and current capacity (unit: A / cm 2 ) and specific current capacity (unit: A cm kg -1 ) were measured. The results are shown in Figures 25 to 28. For comparison, Figures 23 to 28 also show the measurement results of a CNT yarn obtained by spinning a CNT forest not modified with copper microparticles (Cu fraction: 0 vol%) and the results of a general pure copper wiring (Cu fraction: 100 vol%).

[0079] 23 to 28, it was confirmed that the conductive member has better electrical properties than CNT yarn formed only from CNTs. Specifically, when the volume fraction of copper in the conductive member is 30 vol% or more, the electrical conductivity and specific electrical conductivity are substantially similar to those of copper, and when the volume fraction of copper is 35 vol% or more, the current capacity and specific current capacity are substantially similar to those of copper.

[0080] Example 2 (1) Synthesis of spinnable CNT forests Vertically aligned CNTs were grown on a substrate by a two-step floating catalyst CVD method. The details of the synthesis method of spinnable CNT forests have been described in previous reports. In the first step, a solution containing ferrocene, the catalyst precursor of CNTs, in ethanol was ultrasonically atomized and transported to a Si substrate in a CVD chamber by Ar carrier gas. Ferrocene was pyrolyzed on the Si substrate at 700°C to form Fe nanoparticles in-situ. In the second step, acetylene was supplied as a carbon source gas and chlorine gas was supplied for the purpose of lengthening CNTs. A CNT forest with a diameter of 10 nm and a forest length of about 300 μm was synthesized by setting the CNT growth temperature at 700°C and the growth pressure at 18 Torr. The CNT forest obtained in this way was spinnable.

[0081] (2) Cu nanoparticle loading on CNT forests Copper nanoparticles (hereinafter, also referred to as "Cu-NPs") were supported on the CNT forest. Cu(acac)2, a precursor of Cu-NPs, and spinnable CNT forest were placed in a CVD chamber and held at 400°C for 15 minutes in a 100% Ar atmosphere of 30 Torr. In this process, Cu(acac)2 evaporates, diffuses, and pyrolyzes on the CNT surface. Then, it pyrolyzes on the CNT surface, and Cu-NPs are nucleated. Because the vapor of Cu(acac)2 diffuses homogeneously to the inside of the CNT forest, Cu-NPs were also uniformly deposited on the CNTs inside the CNT forest. After supporting Cu-NPs, the chamber was evacuated and reduced at 350°C for 1 hour in a 100 Torr argon:hydrogen = 4:1 atmosphere. In addition, the amount of Cu(acac)2 was changed to control the amount of Cu-NPs supported on the CNT forest. Hereinafter, the spinnable CNT forest obtained in this manner will also be referred to as the "Cu-NPs-supported CNT forest."

[0082] (3) Preparation of Cu-NPs-loaded CNT yarn As in Example 1, when one end of the Cu-NPs-supported CNT forest was pulled out, a CNT bundle (in this specification, a partial structure of the CNT forest, meaning a bundle of several CNTs having adjacent parts) was continuously pulled out, and a unidirectionally oriented CNT linkage (CNT web) was formed. A CNT twisted yarn was produced by pulling out the CNT web with a slider while twisting it. The spindle rotation speed was 14000 rpm, and the pull-out speed was 50 mm / s. Hereinafter, the CNT twisted yarn thus obtained is also referred to as "CNT twisted yarn supported by Cu-NPs". For comparison, a CNT twisted yarn was also produced from a CNT forest not supporting Cu-NPs. Hereinafter, this CNT twisted yarn is referred to as "unsupported CNT twisted yarn".

[0083] (4) Copper plating In order to deposit copper on the CNT strand, an electroplating process was performed on the Cu-NPs-supported CNT strand and the unsupported CNT strand using a copper sulfate solution. A direct current was supplied to the strand, with the copper plate as the anode and the CNT strand as the cathode. The current density was 0.2 A / dm 2 The copper oxide was supplied at 400 sccm and hydrogen at 100 sccm for 2 hours. In order to reduce copper oxide that may be present and to smooth the adhesion between the CNTs and copper, heat treatment was performed at 500 Torr and 700°C for 1 hour while supplying argon at 400 sccm and hydrogen at 100 sccm. In this way, a filamentous conductive member (hereinafter also referred to as "CNT / Cu-wire") was obtained, which includes a CNT continuum (CNT twisted yarn) having a thread shape and a plating-based substance deposited on at least a part of the CNTs that make up the CNT twisted yarn. In this specification, the term "plating-based substance" refers collectively to the plating substance (substance formed by plating) and the substance based on the plating substance (corresponding to the reduced body of the copper plating in this embodiment).

[0084] (5) Characterization A field emission scanning electron microscope (Hitachi, SU-8030) was used to observe the CNTs. A cross-section polisher (JEOL, IB-09020 CP) was used to process the cross-section of the CNTs / Cu-wire to a high quality in order to observe the cross-sectional secondary electron image of the CNTs / Cu-wire. A transmission electron microscope (JEOL, JEM-2100F) was used to observe the cross-section of the CNTs / Cu-wire at high magnification. A thin film of the CNTs / Cu-wire was prepared using a FIB (JEOL, JIB-4700F) to observe the transmission electron image. The electrical conductivity was measured using the four-terminal method under atmospheric pressure. The current capacity was measured using the two-terminal method under high vacuum. If the measurement length of the two-terminal method is short, heat will escape to the electrode, so the measurement length was set to 1 cm in order to measure the current capacity of the true sample. The current density at the time when the yarn broke was taken as the current capacity. The tensile properties were measured using a tensile tester (Shimadzu Corporation, "EZ-L") with 5 measurements, a measurement length of 1 cm, and a tensile speed of 0.05 mm / min. Tensile strain was measured using a non-contact extensometer (Shimadzu Corporation, "TRViewX").

[0085] The measurement results of the CNT / Cu-wire obtained by the above manufacturing method are shown below. (1) Dry-spinning of CNT yarn from Cu-NPs-loaded CNT forest According to the Cu-NPs supporting method of this embodiment, the amount and particle size of Cu-NPs can be controlled by parameters such as the amount of precursor and temperature. Cu(acac)2 is a sublimable organic compound that sublimes and pyrolyzes at a relatively low temperature. Therefore, it can be said that it is suitable as a precursor that diffuses into the inside of the CNT forest by vapor and supports Cu-NPs on the CNT surface throughout the CNT forest.

[0086] However, the conditions for uniformly supporting Cu-NPs even inside the CNT forest must be carefully controlled. The thermal decomposition rate of Cu(acac)2 varies greatly depending on the pressure and temperature inside the chamber. When the temperature is high, the thermal decomposition rate is fast, so the support of Cu-NPs proceeds from the side of the CNT forest, and it is not possible to support Cu-NPs inside the CNT forest. In this example, the conditions for supporting Cu-NPs were carefully examined, and a spinnable CNT forest was obtained in which Cu-NPs were uniformly supported even inside the CNT forest.

[0087] Secondary electron images of CNT forests carrying Cu-NPs when the amount of Cu(acac)2 was changed to 10 mg, 30 mg, and 100 mg are shown in Figures 30(A) to 30(C). As shown in Figure 30(A), when the amount of Cu(acac)2 was as small as 10 mg, the amount of Cu-NPs carried on the CNT surface was small, and there were CNTs that did not carry Cu-NPs. However, the spinnability was high, just like the CNT forests that did not carry Cu-NPs.

[0088] As shown in Figure 30(C), when the amount of Cu(acac)2 was as large as 100 mg, the amount of Cu-NPs supported on the CNT surface was very large. In this case, the CNTs were bonded to each other by Cu-NPs, and the entire CNT forest was a single bonded body. When the end of the CNT forest was pulled out, the CNT bundle adjacent to the pulled CNT was strongly bonded to the CNT forest and could not be separated from the CNT forest. For this reason, continuous dry spinning did not occur, and it was impossible to produce a CNT twisted yarn when the amount of Cu(acac)2 was 100 mg.

[0089] As shown in Fig. 30(B), by using 30 mg of Cu(acac)2, Cu-NPs were evenly supported on the CNT surface, and a CNT forest with high spinnability was obtained. In this example, since it was necessary to spin the CNT yarn, the CNT yarn was produced using a CNT forest manufactured with 30 mg of Cu(acac)2.

[0090] In this example, Cu(acac)2 was used as the precursor because the purpose was to form a composite with copper, but other acetylacetonate complexes (Pt(acac)2, Ni(acac)2, Zn(acac)2, etc.) can be used to support nanoparticles of various metals on the CNT forest in the same way. Therefore, the method according to this example can be used not only for wiring materials, but also for applications such as electrode materials for batteries and capacitors.

[0091] In this embodiment, dry spinning was realized in which Cu-NPs were supported on the entire CNT forest and the drawn CNT web was also supported uniformly with Cu-NPs. In this embodiment, Cu-NPs were supported at the stage of spinnable CNT forest where the distance between CNT bundles is wider than in CNT twisted yarn, so that Cu-NPs can be supported uniformly in the CNT twisted yarn, in contrast to the case where Cu-NPs are supported after the CNT twisted yarn is produced. In the method according to this embodiment, nanoparticles are supported on the CNT forest in advance, so there is a wide range of applications, such as Cu-NPs-supported CNT forest, Cu-NPs-supported CNT sheet, and Cu-NPs-supported CNT twisted yarn. The method used in this embodiment has the advantage of being easy to handle and convenient for users.

[0092] (2) Structural analysis of CNT / Cu-wire A copper luster was observed on the surface of the CNT / Cu-wire obtained by this embodiment. FIG. 31(A) is a diagram showing a cross-sectional secondary electron image of a composite yarn (hereinafter, also referred to as "Mixed CNT / Cu-wire") in which copper is precipitated on a CNT twisted yarn (Cu-NPs-supported CNT twisted yarn) that has Cu-NPs preliminarily supported thereon using CNTs with a diameter of about 10 nm. FIG. 31(B) is a diagram showing a cross-sectional secondary electron image of a composite yarn (hereinafter, also referred to as "Unmixed CNT / Cu-wire") in which copper is precipitated on a CNT twisted yarn (unsupported CNT) that does not support Cu-NPs preliminarily, although it is common in that CNTs with a diameter of about 10 nm are used. In this specification, "CNT / Cu composite yarn" may be used as a general term for Mixed CNT / Cu-wire and Unmixed CNT / Cu-wire.

[0093] As shown in Figure 31(A), in the mixed CNT / Cu-wire, copper was precipitated uniformly from the outer periphery to the inside of the CNT twisted yarn. Moreover, from the high magnification image, it can be seen that copper was precipitated densely. In contrast, in the unmixed CNT / Cu-wire, as shown in Figure 31(B), a core-clad structure (the CNT twisted yarn is the core and the copper is the clad) was formed with a large amount of copper precipitated on the outer periphery of the CNT twisted yarn. Furthermore, copper precipitated in island form was also present inside the CNT twisted yarn. Comparing Figures 31(A) and 31(B), it was confirmed that copper could be precipitated uniformly even inside the CNT twisted yarn by first loading Cu-NPs on the CNT twisted yarn and then plating it.

[0094] Copper ions in the plating solution are likely to precipitate as metallic copper on the surface of Cu-NPs, which is stable in terms of surface energy. In this example, Cu-NPs are formed throughout the CNT twisted yarn, and copper ions diffused inside the CNT twisted yarn during plating precipitate as metallic copper on the surface of Cu-NPs. In addition, since the distance between the CNT bundles of the CNT twisted yarn is about 200 nm, it is considered that copper ions are sufficiently diffused throughout the entire CNT twisted yarn by impregnation with the plating solution before passing current. Furthermore, since the current density during plating is low, the rate-determining process is not ion diffusion but copper precipitation on the CNT surface. Therefore, even after plating begins, ions move further inward and precipitation continues, which is considered to be why homogeneous CNT / Cu-wire was produced in this example.

[0095] A transmission electron image of an orthogonal cross section (cross section perpendicular to the extension direction of the CNT) of the mixed CNT / Cu-wire is shown in FIG. 32(A), and its high-magnification image is shown in FIG. 32(B). As shown in these figures, the particle size of the precipitated copper is several hundreds of nm. It can also be seen that copper precipitates between the CNT bundles and adheres closely to the CNT surface. There were almost no voids between the copper and the CNT, but nanovoids of about several tens of nm existed between the CNT bundles. In addition, from the high-magnification image (FIG. 32(B)), it was observed that the CNT covered with the copper matrix had a slightly crushed shape. From this observation, it was confirmed that even if copper starts to be electrolytically deposited from the Cu-NPs supported on the CNT surface, copper precipitates so as to surround the CNT by the end of plating.

[0096] A transmission electron image of a parallel cross section (cross section in the plane including the extension direction of the CNT) of the mixed CNT / Cu-wire is shown in Figure 33(A), and its high-magnification image is shown in Figure 33(B). As shown in these figures, the CNT and copper were continuously adhered to each other in the longitudinal direction. (3) Electrical conductivity properties of CNT / Cu-wire

[0097] Figure 34(A) shows the electrical conductivity of mixed CNT / Cu-wire and unmixed CNT / Cu-wire at room temperature. For comparison, data for CNT twisted yarn and copper wire (99.99% purity) are also shown. The volumetric copper content of the CNT / Cu-wire, shown on the horizontal axis of Figure 34(A), was calculated by calculating the volume of copper precipitated in the CNT / Cu-wire from the weight increase between the CNT / Cu-wire and the CNT twisted yarn before copper was precipitated, and then dividing this by the volume of the CNT / Cu-wire. Figure 34(B) is a graph in which the vertical axis of Figure 34(A) is made into a linear scale.

[0098] As shown in Figure 34(A), the conductivity of the mixed CNT / Cu-wire is 2.41 × 10 5 S / cm, the conductivity of unmixed CNT / Cu-wire is 4.26×10 4 The electrical conductivity of the CNT yarn was 2.35×10 2S / cm, and the conductivity of copper wire (4.5×10 5 S / cm), which is three orders of magnitude smaller. The conductivity of the CNT / Cu-wire increased as the volume ratio of copper increased. In the linear scale plot shown in Figure 34(B), the mixed CNT / Cu-wire has an almost linear relationship with the copper wire, and free electrons moving in the copper matrix are dominant as carriers. The conductivity of the unmixed CNT / Cu-wire is lower than the linear relationship. The cross-sectional secondary electron image in Figure 31(B) shows that copper precipitated in islands inside the CNT / Cu-wire is present, indicating that copper is present that does not contribute to conductivity. As a result, it is believed that the conductivity decreased relative to the copper content.

[0099] Figure 35 shows the temperature dependence of the electrical resistivity of each sample normalized by the value at 300 K. As shown in Figure 35, the electrical resistivity of the copper wire (dashed line) increases in proportion to the temperature due to phonon scattering, and the temperature coefficient of resistance (TCR) is 3.3 × 10 -3 K -1 The electrical resistivity of the mixed CNT / Cu-wire (solid line) and the electrical resistivity of the unmixed CNT / Cu-wire (dotted line) increase with increasing temperature, but the TCR is 1.2×10 -3 K -1 , 2.0×10 -3 K -1 , which is smaller than that of copper wire. This suggests that phonon scattering of electrons is suppressed by the CNTs. In addition, because the TCR of Mixed CNT / Cu-wire, which has a larger contact surface area between the CNTs and the copper matrix, is smaller than that of Unmixed CNT / Cu-wire, it is expected that phonon scattering of free electrons is reduced near the interface between the CNTs and copper. As shown in Figure 35, when measuring the electrical conductivity in the longitudinal direction, the temperature coefficient of resistance (TCR) in the range from 300K to 450K was 1.8×10 -3 K -1 It is preferable that the value is less than 1.5×10 -3 K -1 More preferably, it is 1.2×10 -3 K -1 It is particularly preferred that:

[0100] Figure 36 shows the temperature dependence of the specific conductivity of Mixed CNT / Cu-wire and copper wire. The specific conductivity of Mixed CNT / Cu-wire (solid line) is smaller than that of copper wire (dashed line) at room temperature (300K) because CNT does not contribute to electrical conduction. However, because the TCR of Mixed CNT / Cu-wire is smaller than that of copper, the specific conductivity of Mixed CNT / Cu-wire reversed that of copper wire at 370K. In other words, it was confirmed that the specific conductivity of Mixed CNT / Cu-wire is stably higher than that of copper wire at 400K or higher.

[0101] On the other hand, as shown in Figure 35, the electrical resistivity of the CNT twisted yarn (dashed line) decreases linearly with increasing temperature, and its TCR is -0.6 × 10 -3 K -1 This negative linear temperature dependence of electrical resistance is thought to be due to the effect of Friedel oscillations.

[0102] The current capacity of each sample is shown in Figure 37. The current capacity of the Mixed CNT / Cu-wire is 1.3×10 5 A / cm 2 The current capacity of the unmixed CNT / Cu-wire is 5.32×10 4 A / cm 2 The current capacity of the mixed CNT / Cu-wire was 5.8×10 4 A / cm 2 ) was about 2.2 times higher. When the current density supplied to the CNT / Cu-wire is increased, the electrical resistance increases due to the generation of Joule heat in the CNT / Cu-wire. As mentioned above, the electrical conductivity of the CNT / Cu-wire is higher than that of copper at high temperatures above 370K, so the Joule heating relative to the current density is smaller than that of copper wire. As a result, the temperature rise is reduced and the current capacity is increased. Thus, as shown in Figure 37, the mixed CNT / Cu-wire has a current capacity of 10 5 A / cm 2 It has been confirmed that this is preferable.

[0103] Figure 38 shows a graph showing the relationship between the specific conductivity and specific current capacity of each sample. The specific conductivity of the Mixed CNT / Cu-wire is 4.31×10 4 S cm 2 / g, and copper wire (4.87 × 10 4 S cm 2 / g) was almost the same as CNT twisted yarn (4.40 × 10 2 S cm 2 / g), which is more than two orders of magnitude higher. The specific conductivity is almost entirely dependent on the copper content. This also supports that the carriers in the composite material are free electrons of copper. On the other hand, the specific current capacity of the Mixed CNT / Cu-wire is 6.5×10 3 2.32×10, which is 3.6 times larger than A cm / g 4 The suppression of the increase in resistance at high temperatures in the CNT / Cu resulted in a significant improvement in transport capacity, even though the current flows through the copper matrix, just like in a copper wire.

[0104] In addition, the CNT twisted yarn (2.85 × 10 4 A·cm / g) was the largest value. CNT twisted yarn has a much higher sublimation temperature than copper, and also has a high infrared emissivity, so it can transport electric current at higher temperatures than copper, and although its specific conductivity is two orders of magnitude smaller than that of copper, it is known to exhibit a high specific current capacity. From the above, Mixed CNT / Cu-wire is lightweight yet has high conductivity, and has a current capacity that surpasses that of copper wire, so it is expected to be used as a thin-diameter wiring capable of supplying high power.

[0105] (4) Mechanical properties of CNT / Cu-wire Table 1 shows the properties of the CNT yarn, CNT / Cu composite yarn, and copper wire.

[0106] [Table 1]

[0107] Figure 39(A) shows the stress-strain curves of the Mixed CNT / Cu-wire and Unmixed CNT / Cu-wire manufactured using CNTs with a diameter of about 10 nm. For comparison, the stress-strain curves of the CNT twisted yarn and copper wire manufactured using CNTs with a diameter of about 10 nm are also shown. The tensile strength of the Mixed CNT / Cu-wire was 699 MPa and the Young's modulus was 70.4 GPa. The tensile strength of the copper wire was 191 MPa and the Young's modulus was 83.5 GPa, while the tensile strength of the CNT twisted yarn was 666 MPa and the Young's modulus was 32.2 GPa. Compared to the CNT twisted yarn, the tensile strength and Young's modulus of the Mixed CNT / Cu-wire were both improved by homogeneous compositing with copper. The tensile strength and Young's modulus of the Unmixed CNT / Cu-wire were 182.9 MPa and 25.8 GPa, respectively, and both the tensile strength and Young's modulus decreased. FIG. 39(B) is a graph showing the relationship between the Young's modulus and the tensile strength of various samples obtained from the stress-strain diagram of FIG. 39(A). As shown in FIG. 39(B), when the CNT twisted yarn is used as a reference, the Young's modulus of the Mixed CNT / Cu-wire is significantly increased, and the tensile strength is equal to or greater than that of the CNT twisted yarn. In contrast, the tensile strength of the Unmixed CNT / Cu-wire is significantly decreased, and the Young's modulus is also decreased. In other words, a comparison between the Mixed CNT / Cu-wire and the Unmixed CNT / Cu-wire shows that the Mixed CNT / Cu-wire, which is a thread-shaped conductive member, has a tensile strength of 1.0 times or more and a Young's modulus of 1.5 times or more, based on the blank carbon nanotube continuum corresponding to the material obtained by removing the plating substance from this thread-shaped conductive member, that is, the CNT twisted yarn. It is more preferable that the Young's modulus of the Mixed CNT / Cu-wire is 2.0 times or more based on the CNT twisted yarn.

[0108] A secondary electron image of the tensile fractured part of the Mixed CNT / Cu-wire is shown in Figure 40(A), and a secondary electron image of the tensile fractured part of the Unmixed CNT / Cu-wire is shown in Figure 40(B). As shown in Figure 40(A), the fractured part of the Mixed CNT / Cu-wire had a short CNT pull-out. On the other hand, as shown in Figure 40(B), the copper in the outer periphery (clad) of the Unmixed CNT / Cu-wire broke and slipped, and the CNT twist was pulled out for a long time. The Mixed CNT / Cu-wire showed a significant improvement in Young's modulus and tensile strength compared to the copper wire, which indicates that not only was copper precipitated homogeneously in the CNT twist, but it also had good adhesion to the CNT bundle surface, and copper, as a matrix, transmitted the load between the CNT bundles well. In other words, by comparing FIG. 40(A) and FIG. 40(B), it was confirmed that the Mixed CNT / Cu-wire can be regarded as a fiber-reinforced composite material with copper as the matrix.

[0109] FIG. 41(A) is a secondary electron image of a composite yarn in which copper is precipitated on a CNT twisted yarn carrying Cu-NPs. FIG. 41(B) is a secondary electron image of a buckling part of a composite yarn in which copper is precipitated on a CNT twisted yarn not carrying Cu-NPs. As shown in FIG. 41(A), the Mixed CNT / Cu-wire can be deformed with a small curvature. This composite yarn is flexible because it is a homogeneous medium in which CNT and copper are homogeneously mixed. On the other hand, as shown in FIG. 41(B), the Unmixed CNT / Cu-wire easily buckles and breaks. This is thought to be because, although the CNT twisted yarn remains intact in the center of the Unmixed CNT / Cu-wire, the CNT twisted yarn portion cannot bear the compressive load caused by bending, and the outer peripheral part (cladding) made of copper on the surface easily buckles.

[0110] As described above, in Example 2, a CNT / Cu composite yarn containing a homogeneous high proportion of CNT was produced. Due to the synergistic effect of CNT and copper, it is an innovative new material that has high electrical conductivity, low TCR, high current capacity, high tensile properties, and high flexibility. Homogeneous CNT / Cu-wire is expected to be a new lightweight wiring material for drone motors, earphones, small coils for small actuators, and wiring for small electronic device systems with high energy density. In addition, the dry CNT spinning technology with vapor-phase nanoparticle deposition shown in this example to obtain a homogeneous composite material is a new technology that adds a new aspect to CNT applications. Since various structures such as long fibers, sheets, and three-dimensional structures can be formed by CNTs carrying nanoparticles, it is possible to apply CNTs with various functionalities in the future. [Explanation of symbols]

[0111] 10: Glass tube 20: Heater 30: CNT Forest 40: Modified CNT forest 50:CNT 60: CNT continuum 70: Fine particles 100: Manufacturing equipment 100A: Plating equipment 110: Mica sheet 120: CNT twisted yarn 130: Copper sulfate bath 141, 142: Clip 151, 152: Wiring 160: Power supply 161: Cathode terminal 162:Anode terminal 170: Anode 200: Conductive material D: Direction RC: Reaction chamber RS: Substances containing metal elements SB: Substrate

Claims

1. a carbon nanotube forest that is spinnable and has carbon nanotubes oriented in a predetermined direction; and a particle supported on the carbon nanotube. It is spinnable, The carbon nanotubes located inside also support the fine particles. A modified carbon nanotube forest comprising:

2. The modified carbon nanotube forest of claim 1 , wherein the ratio R defined by the following formula (1) using the adjacent gap D1 of the carbon nanotubes and the average particle diameter D2 of the microparticles is 3 or more. R=D1 / D2 (1) Here, the adjacent gap D1 is expressed by the following formula (2) using the number density A (unit: tubes / m2) of the modified carbon nanotube forest and the average diameter D3 of the carbon nanotubes, and the average particle size D2 and the average diameter D3 are the arithmetic average of the diameters of the microparticles at 10 or more locations and the arithmetic average of the diameters of the carbon nanotubes at 10 or more locations, respectively, measured by observing the modified carbon nanotube forest using an electron microscope. ..|. -1 / 2 .3())

3. The modified carbon nanotube forest of claim 1 or claim 2, wherein the microparticles are conductive.

4. The modified carbon nanotube forest of claim 1 , wherein the microparticles include an oxide.

5. A carbon nanotube continuous body comprising a spinning body of the modified carbon nanotube forest described in any one of claims 1 to 4.

6. The continuous carbon nanotube body according to claim 5 , wherein the continuous carbon nanotube body has a web shape.

7. The continuous carbon nanotube body according to claim 5 , wherein the continuous carbon nanotube body has a thread shape.

8. The continuous carbon nanotube body according to claim 7 , which is twisted.

9. A modified carbon nanotube forest comprising carbon nanotubes oriented in a predetermined direction and capable of being spun, and microparticles supported on the carbon nanotubes, the modified carbon nanotube forest being capable of being spun, and the carbon nanotubes located inside the modified carbon nanotube forest also supporting the microparticles. a plating-based material deposited on the carbon nanotubes located inside the modified carbon nanotube forest; A conductive member comprising:

10. An interlayer thermally conductive material comprising the electrically conductive member according to claim 9.